Optimalisasi Audit Internal terhadap Siklus Pendapatan dan Pengeluaran Sebagai Pencegahan Kecurangan di Era Digital - Taufikurahman, Taufikurahman; Naila Zalzabilah; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Digital transformation has fundamentally reshaped organizational operational and financial recording processes; however, this advancement also heightens the risk of fraud, particularly within revenue and expenditure cycles. This study aims to analyze the implications of strengthening internal audit through digital and risk-based approaches as a strategic measure to prevent fraud in the digital era. The research employs a literature review method, examining journals, books, and academic publications related to digital auditing, accounting information systems, and risk management. The findings indicate that optimizing internal controls in revenue and expenditure cycles through transaction verification, reconciliation, multi-level authorization, and continuous monitoring significantly reduces fraud risk. The integration of technologies such as accounting information systems, monitoring dashboards, and data analytics enables internal auditors to oversee transactions in real time, detect anomalies, and conduct risk-based audits effectively. The implementation of these strategies not only reinforces internal control but also supports more accurate and evidence-based managerial decision-making. This study emphasizes that the combination of adaptive internal audit practices and digital technologies constitutes a critical foundation for organizations to maintain financial integrity and prevent fraud in the era of digital transformation.